Role of Trans-Cerebral Diameter in Estimation of Gestational Age in Fetuses with Intrauterine Growth Restriction - Dr Rukhsana Babar; Saima Naz; Sadia Salman; Shamaim Rehman; Dil Jan Rehamn; Rabia Mahmood (Shalamar Medical & Dental College, Lahore, Pakistan, 2024)
Background: Determining gestational age is crucial for quality maternal and fetal care. Ultrasonographic measurements of femur length (FL), crown-rump length (CRL), head circumference (HC), and biparietal diameter (BPD) are used for gestational dating. However, these don't correlate well in Intrauterine growth restriction (IUGR) cases. Studies report that trans cerebellar diameter could be used for gestational age estimation in IUGR cases. Objective: To find the correlation between trans cerebellar diameter and gestational age based on the last menstrual period (LMP) in intrauterine growth restriction fetuses. Methods: It was a cross-sectional study. The data was collected from the Department of Obstetrics and Gynecology, Sir Ganga Ram Hospital Lahore from 20 February 2022 to August 2022. After informed consent 60 women aged 18-40 years and parity <5 with suspected Intrauterine growth restriction (IUGR) were included in the study. Gestational age was determined from the LMP while trans cerebellar diameter was by Ultrasonography. The correlation between gestational age and trans cerebellar diameter was determined and compared across subgroups of the study population based on age, parity, and BMI. Results: The mean age of the study participants was 25.6±6.3 years. The majority of the women were primiparous. The mean BMI was 27.8±3.4 Kg/m2. The mean gestational age was 33.35±2.25 weeks. Trans cerebellar diameter range was 36.3 mm to 49.6 mm. A significant correlation was found between gestation age and trans cerebellar diameter (r=0.979, p-value<0.001) in subgroups based on age, parity, and BMI. Conclusion: A significant positive correlation was observed between Trans cerebellar diameter and gestational age among women with IUGR suggesting its routine use in estimating gestational age among high-risk obstetric care patients